Haemophilia early arthropathy detection with ultrasound and haemophilia joint health score in the moderate haemophilia (MoHem) study. Issue 2 (6th February 2021) - Måseide, Ragnhild J.; Berntorp, Erik; Astermark, Jan; Hansen, Jessica; Olsson, Anna; Bruzelius, Maria; Frisk, Tony; Aspdahl, Magnus; Nummi, Vuokko; Tjønnfjord, Geir E.; Holme, Pål A.
Abstract: Introduction: Detection of early arthropathy is crucial for the management of haemophilia, but data on moderate haemophilia are limited. Therefore, we evaluated joint health and treatment modalities in Nordic patients with moderate haemophilia A (MHA) and B (MHB). Aim: To explore and compare the Haemophilia Early Arthropathy Detection with Ultrasound (HEAD‐US) and Haemophilia Joint Health Score (HJHS) to detect early arthropathy in moderate haemophilia. Methods: A cross‐sectional, multicentre study covering Nordic patients with MHA and MHB. Arthropathy was evaluated by HEAD‐US and HJHS 2.1. Results: We assessed 693 joints in 118 patients. HEAD‐US scores (medians [interquartile ranges]) were as follows: elbows 0 points (0–0), knees 0 (0–0) and ankles 0 (0–1). Respectively, by HJHS: elbows 0 (0–1), knees 0 (0–1) and ankles 0 (0–1). Cartilage (14%) and bone (13%) were most commonly affected by HEAD‐US. Frequent HJHS findings were crepitus on motion in knees (39%), and loss of flexion (23%) and extension (13%) in ankles. HEAD‐US correlated strongly with HJHS (elbows r  = .70, knees r  = .60 and ankles r  = .65), but 24% had discordant scores. Joints with HJHS zero points, 5% captured HEAD‐US ≥1 point. Moreover, 26% had HJHS findings without HEAD‐US pathology. Notably, 31% of knees had crepitus on motion and normal HEAD‐US. Conclusion: Overall, the joints attained low scores implying good joint health. HEAD‐US correlated strongly with HJHS. In 5%, HEAD‐US detected subclinical pathology. Crepitus on motion was frequently reported despite normal HEAD‐US, thus not necessarily reflecting arthropathy. HEAD‐US therefore improves the joint assessment in moderate haemophilia.